Advantages of Stretching Before Surgery on the Functionality of the Shoulder after the Surgery in Patients Undergoing Mastectomy - Muhammad Mubashir Ahmed Chandio, Muhammad Abid Owais, Masood Ahmed, Syed Moin Islam Shah, Rafia Unar, Ramsha Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To analyse the effects of stretching the muscles of the shoulder before surgery on the functionality of the shoulder after the surgery of mastectomy Study design: An analytical cross-sectional study Place and Duration: This study was conducted at Bibi Asifa Bhutto Dental College SMBB Medical University CMC Teaching Hospital Larkana from January 2022 to June 2022. Methodology: All the patients included in the study had mastectomy. The participants were randomized to control groups and treatment groups. The participants in the treatment group were gone through static stretching with a range of motion. The control group did not undergo any stretching preoperatively and was given standard postoperative care. The Numeric Pain Rating Scale (NPRS), Groningen Activity Restriction Scale (GARS), and Universal Goniometer (UG) were used for the collection of the data on the first and third postoperative days. The data was analyzed in the IBM SPSS version 26. Results: A total of 20 patients were included in the study. Overall10 patients were allocated to the treatment group and 10 were allocated to the control group. The mean age of the patients was 47±11.86 years. A significant difference in the functionality, range of motion, pain, and Groningen Activity Restriction Scale scores for daily activities was seen in the treatment group (p<0.05)compared to the control group (p>0.05). However, the difference was not significant in external rotation and Groningen Activity Restriction Scale scores (p>0.05). Conclusion: Shoulder stretching before surgery is not only safe, but it is also effective in the reduction of functional restriction and pain after the mastectomy surgery. Keywords: Shoulder stretching, Pre-operative stretching, Mastectomy, Post-op shoulder function